What Is the Point of the Harshness Objection?. Issue 4 (December 2020) - Albertsen, Andreas; Nielsen, Lasse
Abstract: According to luck egalitarianism, it is unjust if some are worse off than others through no fault or choice of their own. The most common criticism of luck egalitarianism is the 'harshness objection', which states that luck egalitarianism allows for too harsh consequences, as it fails to provide justification for why those responsible for their bad fate can be entitled to society's assistance. It has largely gone unnoticed that the harshness objection is open to a number of very different interpretations. We present four different interpretations of the harshness objection in which the problem pertains to counterintuitive implications, badness of outcome, disproportionality, or inconsistency, respectively. We analyse and discuss appropriate luck egalitarian replies. Disentangling these different versions clarifies what is at the heart of this dispute and reveals the point of the harshness objection. We conclude that only the inconsistency version involves a durable problem for luck egalitarianism.